Pengaruh Literasi Budaya terhadap Persepsi Moderasi Beragama Generasi Z di UIN Sunan Ampel Surabaya (Journal of Islamic Thought and Philosophy, 2026)
This study aims to analyze the influence of cultural literacy on the perception of religious moderation among Generation Z at the State Islamic University (UIN) Sunan Ampel Surabaya. The research is grounded in the importance of cultural literacy in fostering tolerance, openness, and national commitment in the rapidly evolving digital era. A quantitative correlational approach was employed, involving a population of 6,297 UINSA library visitors and a sample of 98 respondents determined using Slovin’s formula. Data were collected through a Likert-scale questionnaire measuring cultural literacy (understanding diversity, cultural sensitivity, and cross-cultural interaction) and religious moderation (national commitment, tolerance, anti-violence, and accommodation of local culture). The findings indicate a positive and significant effect (path coefficient = 0.900; T-Statistic = 24.708; p-value = 0.000) with an R-Square of 0.811, highlighting cultural literacy as a key determinant.